Beyond abortion Roe v. Wade and the battle for privacy - Ziegler, Mary, 1982- (Harvard University Press, 2018)
More than four decades into the culture wars, Roe v. Wade has become shorthand for the American abortion debate. Rights to Privacy: The Forgotten Legacy of Roe v. Wade illuminates an entirely different and unexpected legacy of America's most controversial Supreme Court decision. Drawing on archives and extensive interviews with key participants, Rights to Privacy opens a window onto an intense debate about the right to privacy that continues to this day. In the 1970s and beyond, activists set out bold ideas about government responsibility, sexual consent, consumer rights, digital data, individual identity, and end-of-life care. These unanticipated visions of a right to choose gradually (but never completely) gave way to a more limited freedom from government. Ziegler captures the rise of contemporary ideas about privacy, all the while explaining the continuing hold that this right--and Roe--have on the public imagination.--